Analisis Profil Terapi dan Evaluasi Kualitas Peresepan Pada Pasien COVID-19 Rawat Inap di Rs X Jawa Tengah: Therapeutic Profile Analysis and Prescription Quality Assessment for COVID-19 Inpatients Hospital X in East Java - Mawarni, Okky Intan; winartiana, Winartiana; Putri, Elsa Mahardika; Pratiwi, Maharani Dwi; Prabowo, Pulung; Ratnanigrum, Elly Rakhmawati (Universitas Kadiri, 2025)
COVID-19, caused by SARS-CoV-2, has a high transmission and mortality rate, The variability in therapies administered to patients necessitates an evaluation of treatment patterns among COVID-19 patients to ensure effective therapeutic outcomes. This study aims to analyze the therapy profiles and evaluate prescription patterns of hospitalized patients at General Hospital X, Central Java, based on the COVID-19 Management Protocol, 2nd edition (January 2021). A retrospective descriptive method with purposive sampling was applied to 100 hospitalized COVID-19 patients in 2022. The results showed that the majority of patients were male (55%), aged 40–59 years (45%), had moderate disease severity (77%), a treatment duration of 1–10 days (89%), and a recovery rate of 62%. The most frequently used drug therapies included respiratory medications (19%), gastrointestinal drugs (17%), vitamins (16%), antibiotics (11%), and antivirals (11%). Prescription evaluation revealed 100% drug suitability, 100% correct dosage, 97% appropriate dosing intervals, and 92% correct duration of administration.